2023
DOI: 10.1037/emo0001163
|View full text |Cite
|
Sign up to set email alerts
|

The role of uncertainty, worry, and control in well-being: Evidence from the COVID-19 outbreak and pandemic in U.S. and China.

Abstract: Uncertainty about the future often leads to worries about what the future will bring, which can have negative consequences for health and well-being. However, if worry can act as a motivator to promote efforts to prevent undesirable future outcomes, those negative consequences of worry may be mitigated. In this article, we apply a novel model of uncertainty, worry, and perceived control to predict psychological and physical well-being among four samples collected in China (Study 1; during the early COVID-19 ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Likewise, high perceived efficacy can mitigate against the negative impacts of worry on mental wellbeing by enabling worry to fulfil its motivational goal of preventing undesirable outcomes. This argument is supported by evidence from an international study showing that worry about COVID-19 risk was more strongly linked with diminished wellbeing among people who felt they had little or no control over their risk of contracting coronavirus (Howell et al, 2022). We therefore hypothesized that: H3: Efficacy beliefs moderate the relationship between climate change worry and mental wellbeing, whereby the negative relationship between climate change worry and mental wellbeing is stronger among people with low perceived efficacy.…”
Section: Efficacy Beliefs Worry and Mental Wellbeingmentioning
confidence: 94%
“…Likewise, high perceived efficacy can mitigate against the negative impacts of worry on mental wellbeing by enabling worry to fulfil its motivational goal of preventing undesirable outcomes. This argument is supported by evidence from an international study showing that worry about COVID-19 risk was more strongly linked with diminished wellbeing among people who felt they had little or no control over their risk of contracting coronavirus (Howell et al, 2022). We therefore hypothesized that: H3: Efficacy beliefs moderate the relationship between climate change worry and mental wellbeing, whereby the negative relationship between climate change worry and mental wellbeing is stronger among people with low perceived efficacy.…”
Section: Efficacy Beliefs Worry and Mental Wellbeingmentioning
confidence: 94%
“…A study, which was based on the feeling-is-for-doing theory of emotions, conjectured (and discovered) that a person's level of ambiguity about their risk of catching COVID-19 would lead to increased anxiety about the virus and that increased anxiety would then indicate a lower quality of life. The study also postulated-and found some evidence for-that worries were associated with lower well-being when people believed they had no control over their risk of getting COVID-19 6 .…”
Section: Introductionmentioning
confidence: 94%
“…For instance, Chirumbolo et al noted negative relationships between job insecurity, life uncertainty, and individual well-being (Chirumbolo et al, 2022). Moreover, Howell et al found that uncertainty about one's COVID−19 risk predicted more significant worry about the virus and one's risk of contracting it and that greater worry would, in turn, predict poorer well-being (Howell et al, 2022).…”
Section: The Mediating Role Of Subjective Well-beingmentioning
confidence: 99%